Radio frequency transistors principles and practical applications - Dye, Norm, 1929- (EDN series for design engineers., 2001)
Radio Frequency Transistors: Principles and Practical Applications is a complete tool kit for successful RF circuit design. As cellular and satellite communications fields continue to expand, the need for RF circuit design grows. Radio Frequency Transistors contains a wealth of practical design information based on years of experience from authors who have worked with the leading manufacturers of RF components. The book focuses primarily on the more difficult area of high power transistor amplifier design and construction.An entire chapter devoted solely to LDMOS high power RF transistors has.